Anti-Inflammatory Effects of Shenfu Injection against Acute Lung Injury through Inhibiting HMGB1-NF-κB Pathway in a Rat Model of Endotoxin Shock. (3rd November 2019) - Liu, Xia; Ai, Fei; Li, Hui; Xu, Qin; Mei, Liyan; Miao, Jifei; Wen, Quan; Zhang, Chaoying; Zhang, Saixia; Zhou, Jianhong; Chen, Xiangyun; Chu, Chunwei; et al.
Abstract : Shenfu injection (SFI), a Chinese herbal medicine with substances extracted from Ginseng Radix et Rhizoma Rubra and Aconiti Lateralis Radix Praeparata, is widely used as an anti-inflammatory reagent to treat endotoxin shock in China. However, the mechanism of SFI in endotoxin shock remains to be illuminated. High mobility group box 1 (HMGB1), a vital inflammatory factor in the late stage of endotoxin shock, may stimulate multiple signalling cascades, including κ B (NF- κ B), a nuclear transcription factor, as well as tumour necrosis factor (TNF)- α and interleukin (IL)-1 β, among others in the overexpression of downstream proinflammatory cytokines. An investigation into the effects of SFI on the inhibition of the HMGB1-NF- κ B pathway revealed the contribution of SFI to acute lung injury (ALI) in a rat model of endotoxin shock. To assess the anti-inflammatory activity of SFI, 5 ml/kg, 10 ml/kg, or 15 ml/kg of SFI was administered to different groups of rats following an injection of LPS, and the mean arterial pressure (MAP) at 5 h and the survival rate at 72 h were measured. 24 h after LPS injection, we observed pathological changes in the lung tissue and measured the mRNA expression, production, translocation, and secretion of HMGB1, as well as the expression of the NF- κ B signal pathway-related proteins inhibitor of NF- κ B (I κ B)- α, P50, and P65. We also evaluated the regulation of SFI on the secretion of inflammatory factors including interleukin-1 beta (IL-1 β ) and TNF- α . SFI effectively prevented the drop in MAP, relieved lung tissue damage, and increased the survival rate in the endotoxin shock model in dose-dependent manner. SFI inhibited the transcription, expression, translocation, and secretion of HMGB1, increased the expression of toll-like receptor (TLR4), increased the production of I κ B- α, and decreased the levels of P65, P50, and TNF- α in the lung tissue of endotoxin shock rats in a dose-dependent manner. Furthermore, SFI decreased the secretion of proinflammatory cytokines TNF- α and IL-1 β . In summary, SFI improves the survival rate of endotoxin shock, perhaps through inhibiting the HMGB1-NF- κ B pathway and thus preventing cytokine storm.